Three essays on resource and development economics in Sub-Saharan Africa: evidence from Senegal - Magbond, Kadoukpe (School of Economics, 2025)
The thesis provides empirical evidence of the contribution of basic infrastructure resources to economic development in Senegal. In addition to the introduction and conclusion, three distinct papers make the backbone of the thesis, the first two being impact evaluation studies. The first paper combines difference-and-difference and propensity score matching and uses quantile regressions to examine the welfare effects of rural electrification. The latter is embedded within the first phase of the Emergency Programme for Community Development (PUDC I) implemented by the Senegalese Government. The study uses a panel dataset of 1,115 rural households observed before and after the roll-out of the program. Findings reveal that rural electrification is an agent of household well-being upgrading, irrespective of the electricity source, whether off-grid or on-grid. Electrified households seem to have enjoyed higher agricultural employment and non-food expenditure compared to the observationally similar households that are not connected to electricity. Social benefits manifested through an increase in school enrolment, school attendance, and time spent by children studying at home, with the increase in school attendance being more pronounced for girls than for boys. Furthermore, poor households and those that have access to a marketplace drew the most substantial benefits from access to electricity. The second paper focuses on water infrastructures. It employs a panel dataset of 1,319 Senegalese rural households to empirically document the welfare effect of piped water adoption. Unlike the first paper which considers both economic and social outcomes, the second paper mainly centers on the economic benefits of piped water adoption, which are employment and household expenditure growth. This is because many previous studies have already looked at the social implications associated with access to water resources. The current gap in the literature is mainly observed with the economic impacts of access to water supply infrastructures installed in rural and under-serviced communities within the developing world. A key finding reveals that the adoption of piped water triggered agricultural employment in the PUDC rural areas. Such benefits appear to be greater within households that have access to road infrastructure, alongside access to water resources. The empirical analyses further suggest that non-poor households seem to benefit more from access to water infrastructures than poor households. Finally, when comparing the welfare effect of government-led PUDC water supply with that of community-led initiatives, our findings suggest that the former is much effective than the latter in improving economic outcomes. Using an array of empirical strategies including descriptive statistics, propensity score matching, quantile regressions, and Blinder-Oaxaca counterfactual decomposition, the third paper unravels the nexus between power outages, firm productivity, and gender-based productivity gap. For many developing countries, power outages represent additional costs for firms, given their need to invest in alternative inputs (i.e., generators) to maintain or enhance performance. Moreover, firms managed by females are often claimed to be more severely hit by such outages given the structural and institutional constraints women face in many developing countries. Understanding these interactions is the purpose of this paper. The World Bank's Enterprise Survey (WBES) dataset which comprises 601 Senegalese establishments surveyed in 2015 is used. The results highlight that female-owned firms underperform compared to male-owned firms and that the scale inefficiency stands out as the root of Senegalese firms' low productivity. A key finding is that unexpected and repetitive interruptions of electricity are sources of Senegalese firms' counter-performance and a driver of a broad gender-based productivity gap within firms.